Oxidative Metabolism Indices in Pigs and Piglets’ Liver Fragments Following their Cryopreservation in Presence of Polyethylene Oxides - Galchenko, S. Ye. (Problems of Cryobiology and Cryomedicine, 2004)
The effect of cryopreservation on the integrity of some bioenergetic indices of pig and piglet liver fragments was studied. It was found that the relative normalisation of metabolic parameters of cryopreserved liver fragments is observed by 60 min after thawing. During the second hour of observation the gradual loss of metabolic properties of the tissue took place. In addition, these processes went in faster way in cryopreserved fragments than in the control, but they did not differ in quality. This phenomenon should be taken into consideration while using liver fragments as model or for other purposes.